苏东牧二校高中二年级学生使用汉语形容词 “严格” 与 “严厉” 的偏误分析 Kesalahan Penggunaan Kata Sifat "Yange" dan "Yanli" pada Siswa Kelas XI SMA Sutomo 2 Medan - Dewi Kartika Tjong (Journal of Language, Literature and Teaching, 2022)
AbstractThis study aims to explain the types and factors that cause errors in the use of the adjectives "yange" and "yanli" in class XI students of SMA Sutomo 2 Medan. Researchers used a qualitative descriptive research design with 30 students as research subjects. The data collection technique used was an elicitation technique to answer the first problem formulation regarding the types of errors and interview techniques to answer the second problem formulation, namely regarding the factors that cause errors. The results showed that there were 3 types of errors in the use of the adjectives "yange" and "yanli" in class XI students of SMA Sutomo 2 Medan, namely the addition of 2 sentences (4.88%); selection errors of 32 sentences (78.05%), and sequencing errors of 7 sentences (17.07%). The total errors in the use of the adjectives “yange” and “yanli” are 41 sentences. The types of errors that appear most often are election errors with a total of 32 sentences (78.05%); while the factors causing the error consisted of interlingual factors with a total of 11 students (45.83%) and intralingual factors with a total of 13 students (54.17%), which consisted of: overgeneralization of 2 students (8.34%) and the wrong concept hypothesis 11 students (45.83%).Key Word: Error; Adjective; “Yange”, “Yanli”